Attitude toward food in aspect of risks and benefits related to the consumption of edible insects by Polish consumers - Joanna Bartkowicz (National Institute of Public Health - National Institute of Hygiene, 2020)
Background. This study is an introduction to the of learning key factors affecting the process of acceptance of edible insects by Polish consumers, currently only from Gdańsk, Gdynia and Sopot (the Tri-City) in northern Poland. Objectives. The aim of this study was to assess the attitudes of Tri-City consumers towards edible insects. It was expressed in the assessment of food diversity in relation to eating benefits of edible insects and to assessment of the levels of dietary neophobia for consumers who perceive the risk of eating them. This study contributes to consumers' getting used to edible insects. Material and methods. The study was carried out in 2015 among 788 participants ranged from 16 to 80 years. The criterion for participation was the place of residence - the Tri-City. The respondents were qualified in three age groups 16-20 years old, 21-40 years old and over 41 years old. The study was conducted using a survey method. The survey questionnaire included the following scales: the Food Neophobia Scale (FNS) and the Variety Seeking Tendency Scale (VARSEEK) perceiving benefits and perception of health hazards associated with the consumption of edible insects compared to traditional and culturally foreign food. Results. The majority of seekers with a high degree of VARSEEK were men aged 21-40 with higher education. The degree of search for diversity in food significantly depended on factors such as gender, age and education. Gender statistically significantly differentiated the opinions of the respondents regarding the health benefits conditioned by the consumption of various products only in the case of snakes and crickets. A statistically significant effect of age on the opinions of respondents regarding health benefits was shown, which was related to the consumption of: snakes, locusts, horse, tarantula. Whereas it was highly significant when it comes to consumption of: snails, crickets, poultry, beef and pork was demonstrated. Age and education were the factors that had a significant influence of the neophobia level, while gender did not have a significant influence. Conclusion. Respondents from the Tri-City were characterized by high openness to new food. The 21-40 age group with university education was particularly outstanding. More women than men had low levels of neophobia. At the same time, it was mainly men who were looking for diversity in food. The obtained results try to explain the issue of acceptance conditions of a new and rather controversial product, which are edible insects to the inhabitants of Europe.